Secular changes in body size and body composition in schoolchildren from La Plata City (Argentina) - Guimarey, Luis Manuel (2014)
Aim: to analyze the secular changes in body size and composition of two cohorts of children from La Plata City, Argentina, with a 35-year follow-up. Subjects and methods: Cohort 1 (C1) was measured in 1969–1970 and included 1772 children (889 boys, 883 girls), and Cohort 2 (C2), measured in 2004–2005, included 1059 children (542 boys, 517 girls). Both cohorts were obtained from matching geographical areas and comprised children from 4 to 12 years. Body weight (W); Height (H); Upper arm circumference (UAC); Tricipital (TS) and Subscapular skinfolds (SS) were measured, and Body Mass Index (BMI) and muscle (UMA) and fat (AFA) brachial areas were calculated. Prevalence of overweight and obesity was estimated by IOTF. To compare C1-C2 we used a generalized linear model with logtransformed variables, and chi square test. Results: There were significant and positive differences between C2-C1 in W, UAC, SS, TS, and AFA. In contrast, H was not significantly different and UMA was significantly different but with negative values. The prevalence of overweight and obesity was 14.5 % and 3.8 % in C1, and 17.0 % and 6.8 % in C2. Differences between cohorts were significant for obesity. Conclusion: The shifts observed for soft tissues – positive trend for fat and negative for muscle area – occurring without changes in height lead us to suppose that in these three decades, La Plata’s population has experienced deterioration in living conditions and important changes in their lifestyle, such as an increased consumption of energy-dense foods and sedentary habits.